2019
DOI: 10.1080/02619768.2019.1576626
|View full text |Cite
|
Sign up to set email alerts
|

Supporting collaborative reflection in teacher education: a case study

Abstract: The aim of this paper is to understand how certain educational supports promote preservice teachers' learning to reflect in collaborative settings. To address this issue, we present a case study on collaborative reflection among 14 preservice teachers and one teacher educator over the course of five weekly consecutive sessions. The results suggest that collaborative reflection can be supported by organizing the process according to a twofold dynamic: from analysis to synthesis, and from open facilitation to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 35 publications
1
21
0
20
Order By: Relevance
“…However, there are studies that have come up with contradictory results about the effectiveness of knowledge sharing in promoting reflectivity. While some authors argue that teacher collaboration improves deeper reflection (Attard, 2012;Clarà et al, 2019), others have reported relatively low-level reflection (Killeavy & Moloney, 2010;Wopereis et al, 2010;Loh et al, 2017) and some concluded that they did not find any conclusive evidence with respect to the influence of teachers' collaboration on their practice (e.g., Parsons & Stephenson, 2005). To meet this knowledge gap, the present study aimed at investigating the effect of using knowledge sharing in a focus group on EFL student teachers' reflective practice.…”
Section: Literature Reviewmentioning
confidence: 89%
“…However, there are studies that have come up with contradictory results about the effectiveness of knowledge sharing in promoting reflectivity. While some authors argue that teacher collaboration improves deeper reflection (Attard, 2012;Clarà et al, 2019), others have reported relatively low-level reflection (Killeavy & Moloney, 2010;Wopereis et al, 2010;Loh et al, 2017) and some concluded that they did not find any conclusive evidence with respect to the influence of teachers' collaboration on their practice (e.g., Parsons & Stephenson, 2005). To meet this knowledge gap, the present study aimed at investigating the effect of using knowledge sharing in a focus group on EFL student teachers' reflective practice.…”
Section: Literature Reviewmentioning
confidence: 89%
“…However, there are studies that have come up with contradictory results about the effectiveness of knowledge sharing in promoting reflectivity. While some authors argue that teacher collaboration improves deeper reflection (Attard, 2012;Clarà et al, 2019), others have reported relatively low-level reflection (Killeavy & Moloney, 2010;Wopereis et al, 2010;Loh et al, 2017) and some concluded that they did not find any conclusive evidence with respect to the influence of teachers' collaboration on their practice (e.g., Parsons & Stephenson, 2005). To meet this knowledge gap, the present study aimed at investigating the effect of using knowledge sharing in a focus group on EFL student teachers' reflective practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ello significó asumir la necesidad de extender la discusión acerca de los límites y alcances de la formación inicial docente con el resto de los académicos de nuestras instituciones. Del mismo modo, implicó que, considerando que el tiempo en los espacios de reflexión con ellos es escaso para la cantidad de problemáticas que los estudiantes traen, aprendimos a organizar mejor la actividad conjunta (Clarà, Mauri, Colomina & Onrubia, 2019) en relación a los propósitos de cada espacio formativo.…”
Section: Algunas Reflexiones Finalesunclassified